A Review on Finite Element Modeling and Simulation of the Anterior Cruciate Ligament Reconstruction - Benos, Lefteris; Stanev, Dimitar; Spyrou, Leonidas; Moustakas, Konstantinos; Tsaopoulos, Dimitrios E. (Frontiers in Bioengineering and Biotechnology, 2020)
The anterior cruciate ligament (ACL) constitutes one of the most important stabilizing tissues of the knee joint. Its rapture is very common and usually occurs in sports involving sudden changes in directions. Given the ACL poor healing capacity, various surgical procedures have been proposed. Undoubtedly, the reconstruction of ACL from a graft yields the best outcome. The rapid progress related to the biomechanics and biology in graft incorporation, fixation devices and ACL substitutes contributed to the establishment of the ACL reconstruction (ACLR). Taking into account the complicated nature of this procedure and the high cost of experiments, computational methods can become a valuable tool for evaluating the surgical procedure in a pre-clinical setting. In particular, finite element (FE) simulations can be used to assess the biomechanical consequences of different surgical techniques and investigate important factors affecting ACLR outcomes. To this end, the present study summarizes the current advancement in both ACLR and its FE simulation. This review emphasizes on the material modelling and properties of the most popular grafts as well as modelling of different surgery techniques, including the number of bundles, fixation devices and initial graft tension.